MC The Newsletter of Masscomm 2024: volume 2 - Khamis, Muhamad Hanapi; Abu Bakar, Muhammad Nabihan; Ismail, Siti Nasarah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Welcome to our eBuletin Volume 2 from Faculty of Communication and Media Studies, UiTM Rembau for this year! As editor, I’m thrilled to share this edition with you. We have packed it with interesting articles, updates, and highlights that capture our community’s dynamic vitality in media technology and behavioural communication. Our objective is to keep you informed, engaged, and inspired, whether you’re reading the latest news or looking for fresh ideas. This issue is particularly remarkable since it captures not just the voices of our great team, but also the pulse of our everchanging community. This ebuletin demonstrates the hard work and ingenuity of our contributors, and I hope it adds value to your day. I appreciate your ongoing support and engagement. Happy Reading!